An Evaluatıon Of Sagıtal And Vertıcal Dentofacıal Effects In Bonded Rapıd Palatal Expansıon Cases - Sevil Akkaya; Sumru Hızlan Lorenzon (Galenos Yayinevi, 1996)
Hyrax appliances to which posterior bite planes have been added are used in the correction of bilateral posterior cross-bites. This study was carried out in order to evaluate sagital and vertical effects of RME. Patients having maxillary bilateral cross-bites, concurrently showing a Angle Class I or a Class II molar relationship were selected. Lateral cephalograms and hand-wrist radiographs which were taken at the beginning of treatment, at the end of treatment and at the end of retention period of 12 patients formed the material of the research. At the beginning of treatment, the average chronological ages were 11.96 years. At the end of the research period; in relation to the cranial base the maxilla moved forward, whereas the mandible showed a downward and backward rotation. Increases in both, the interincisal angle and the amount of overjet was observed.